2014
DOI: 10.1111/eth.12342
|View full text |Cite
|
Sign up to set email alerts
|

Basking Activity is Modulated by Health State but is Constrained by Conspicuousness to Predators in Male Spanish Terrapins

Abstract: Aerial basking may have several benefits for freshwater turtles in addition to thermoregulation such as removing parasites from the skin, which would improve health state. However, basking outside of water may be risky because it may expose freshwater turtles to terrestrial predators. Here, we monitored the basking activity of male Spanish terrapins (Mauremys leprosa) in a wild population of the south‐western of the Iberian Peninsula. We also measured body size, health state parameters, parasite prevalence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…If warmer ponds also had fewer basking spots than cooler ponds, the costs of finding a basking location would increase while the benefit of basking would decrease. Not basking may also have the added benefit of reducing predation risk to terrestrial predators (Ibáñez et al ). Having fewer basking sites coupled with reduced need to bask could thus increase the proportion of adult females by reducing predation associated with basking.…”
Section: Discussionmentioning
confidence: 99%
“…If warmer ponds also had fewer basking spots than cooler ponds, the costs of finding a basking location would increase while the benefit of basking would decrease. Not basking may also have the added benefit of reducing predation risk to terrestrial predators (Ibáñez et al ). Having fewer basking sites coupled with reduced need to bask could thus increase the proportion of adult females by reducing predation associated with basking.…”
Section: Discussionmentioning
confidence: 99%
“…Basking promotes a number of health parameters in ectotherms. Male Spanish terrapins ( Mauremys leprosa ) infected with Hepatozoon were more likely to be found basking (Ibáñez et al, 2015). Basking, however, is a more vulnerable position from a predation standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatozoon (Coccidia: Hepatozoidae) demonstrate higher levels of basking activity and have lower leukocyte volumes than unparasitized individuals. Ibáñez et al (2015) suggested that increased basking may serve to strengthen immune systems in parasitized individuals; they further noted that males with bright limb stripe coloration bask less than those more conspicuously colored, and suggest that color conspicuity may increase predation risk for parasitized individuals.…”
Section: 11mentioning
confidence: 99%